INDONESIAN AND THAI RESEARCH ARCHAEOLOGISTS IMPRESSED WITH SUNGAI BATU ARCHAEOLOGICAL SITE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 3 December 2015 – A senior researcher at the Indonesian National Research Centre for Archaeology, Professor Dr Harry Truman Simanjutak together with a lecturer from the Department of Archaeology, Slipakorn University in Thailand, Professor Dr Rasmi Shoocongdej were impressed with the discovery made by the Centre for Global Archaeological Research (PPAG) Universiti Sains Malaysia (USM) concerning the historical site of Sungai Batu in Merbok, Kedah.